2017
DOI: 10.1371/journal.pone.0181781
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between movement speed and duration during soccer matches

Abstract: The relationship between the time duration of movement (t(dur)) and related maximum possible power output has been studied and modeled under many conditions. Inspired by the so-called power profiles known for discontinuous endurance sports like cycling, and the critical power concept of Monod and Scherrer, the aim of this study was to evaluate the numerical characteristics of the function between maximum horizontal movement velocity (HSpeed) and t(dur) in soccer. To evaluate this relationship, GPS data from 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…1). Despite previous research on duration specific maximal running performance existing in Gaelic football [12], Australian football [24], and soccer [13], the variability of moving average methodology analyses (i. e. MMS and MMP met ) has yet to be investigated. The variability of at least four (i. e. 4, 6 and 10) matches in MMS (4.9-8.4 %; ▶table 2) and MMP met (4.4-9.6 %; ▶table 3) values when compared to that of absolute high-speed running dis-tance values suggests that maximal mean running performance values provide greater reliability in the mode of match running performance analysis and therefore are a reliable alternative for match running performance analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Despite previous research on duration specific maximal running performance existing in Gaelic football [12], Australian football [24], and soccer [13], the variability of moving average methodology analyses (i. e. MMS and MMP met ) has yet to be investigated. The variability of at least four (i. e. 4, 6 and 10) matches in MMS (4.9-8.4 %; ▶table 2) and MMP met (4.4-9.6 %; ▶table 3) values when compared to that of absolute high-speed running dis-tance values suggests that maximal mean running performance values provide greater reliability in the mode of match running performance analysis and therefore are a reliable alternative for match running performance analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ignore a soccer playerʼs capacity to achieve greater running speeds during a period of a match where less distance may be reported. As a result, moving-average analysis methodologies have recently been explored to understand maximum maintainable running speeds over a specific duration [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In cycling, bicycle-mounted power meters enable the direct measurement of rider work intensity. The power or velocity data for each athlete can be summarized as a “mean maximal power (MMP) profile” or “record power profile” ( Quod et al, 2010 ; Pinot and Grappe, 2011 ) or, equivalently, a mean maximal velocity profile ( Delaney et al, 2015 ; Roecker et al, 2017 ). These profiles are predictive of future performances ( Quod et al, 2010 ) and evolve as the athlete develops over time ( Pinot and Grappe, 2015 ), such that unrealistic increases in the powers sustainable for the indicated durations could serve as evidence for doping.…”
Section: Performance As a Marker For Doping Detectionmentioning
confidence: 99%
“…Previous research in soccer [20], Australian football [21], and Gaelic football [22] has demonstrated that maximal mean analyses (i. e. rolling averages) during match play can be used to monitor performance and assist in training prescription. More recently, analyses using shorter time windows through maximal mean analyses (i. e. 1, 5 and 10 s) has been shown to determine an individual's capacity to achieve and maintain both speed and P met at higher running speeds [19].…”
Section: Introductionmentioning
confidence: 99%